Sistem Informasi Pemilihan Karyawan Terbaik Menggunakan Metode Simple Additive Weighting (SAW) pada Balai Pendidikan dan Pelatihan Ilmu Pelayaran BP2IP Malahayati - Rahmatillah, Syaukas; Fadhli, M (Yayasan Kawanad, 2022)
The purpose of this research is to assist the Balai Pendidikan dan Pelatihan Ilmu Pelayaran (BP2IP) Malahayati to process data on the selection of the best employees to computerize the current system so that it can analyze and assist database processing activities at an even better level of effectiveness and efficiency, so that it is expected to be able to ; designing the best web-based Employee Decision Making System (DSS) Application program, the best Employee Decision Making System (DSS) system made in the form of a questionnaire with several alternatives and criteria as basic ingredients in data processing using the Simple Additive Weighting (SAW) Method, and generate reports - more detailed ranking reports, criteria, alternatives, and employees of each required data. Based on the results of the research and decision-making system using the Simple Additive Weighting (SAW) method as the selection of the best employees at the Balai Pendidikan dan Pelatihan Ilmu Pelayaran (BP2IP) Malahayati which has been carried out by the author, several conclusions can be drawn, namely; This research succeeded in creating a decision support system for evaluating the best employee selection at the Balai Pendidikan dan Pelatihan Ilmu Pelayaran (BP2IP) Malahayati, and this research succeeded in conducting alternative rankings from the results of calculating the weight of employee scores using SAW (Simple Additive Weighting).